Improving Student Learning Motivation in Islamic Education Learning Using the Video Based Learning Method at SD Negeri 105436 Paya Pinang - Leginem; Khairunnisa, Siti; Ashiri, Nur Auliah (Journal of Indonesian Primary School, 2024)
This study aims to improve students' learning motivation in Islamic religious education learning by using Model Based Learning. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were elementary school students. The data for this study were obtained by test and observation techniques. Tests are used to measure learning motivation and observations are used to analyze teacher and student learning activities. The data analysis technique used in this study is descriptive statistics by comparing the results obtained with indicators of research success. The results of the study indicate that Model Based Learning can improve students' learning motivation in Islamic religious education learning. This can be seen from the increase in the percentage of student learning completion in each cycle with details of the pre-cycle 40.89%, the first cycle 68.87% and in the second cycle it increased to 90.32%. Thus, the use of Model Based Learning can be used as an alternative to improve students' learning motivation in Islamic religious education learning.